The Glastonbury Thorn in Vernacular Christianity and Popular Tradition - Cusack, Carole M. (Journal for the Study of Religion, Nature and Culture, 2018)
This article considers the most famous English sacred tree, the Glastonbury Thorn, which has a special place in vernacular Christianity and popular folklore. It was part of the pilgrimage site at Glastonbury during the Middle Ages and after the Reformation, Puritan soldiers chopped it down during the Civil War (1642-1651). However, elaborate folklore concerning the Thorn developed between the seventeenth and nineteenth centuries.  according to these tales, Jesus came to Britain with his mother's uncle, Joseph of Arimathea, who planted the Glastonbury Thorn. The Thorn is considered miraculous, as it flowers twice yearly, with the second flowering in winter at Christmas. It also plays multiple roles in England's past and present. For example, all Christian traditions that assert that Jesus walked on soil other than that of the Middle East are engaged in the sacralization of territory, the transformation of the periphery into the center. English tales that claim Jesus visited Somerset and Cornwall bestow upon England the status of a 'Holy Land'. Further, the Thorn is part of the web of connections linking Glastonbury with the English Crown. This article considers the symbolism of the Glastonbury Thorn and assembleshistorical accounts, folklore, and popular cultural practices to investigate its historical importance and its contemporary significance.